Women, Religion, and Education in Early Modern Italy. Some Case Studies (16th-18th c.) - Salomoni, David (Studi sulla Formazione/Open Journal of Education, 2019)
The problem of the female presence in the world of early modern schools has attracted growing historiographic interest in recent years. However, a comparative approach to the study of the female religious orders of teachers in the post-Tridentine age is difficult to establish. This article aims to analyze, in the light of the most recent historiographic acquisitions, the educational experience of some Italian female religious orders at that time, in particular the Ursuline Nuns and the Venerini Pious Teachers. The method of investigation adopted will take into consideration the most significant examples on the Italian peninsula trying to consider the cultural, economic, geographical and chronological differences that characterized these pedagogical experiences. The intention is to bring out the plurality of female educational experiences in Italy and at the same time the common denominators.